2003
DOI: 10.1034/j.1600-0722.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the endothelium on the vasorelaxant response to acetylcholine and vasoactive intestinal polypeptide in the isolated rabbit facial artery

Abstract: The aim was to examine the influence of the endothelium on acetylcholine (ACh) and vasoactive intestinal polypeptide (VIP) functional responses in the isolated glandular branch of rabbit facial artery precontracted with phenylephrine as well as the potential contribution of nitric oxide (NO) and prostanoids in the ACh- and VIP-induced effects. Acetylcholine caused endothelium-dependent and VIP endothelium-independent relaxations of facial artery. The effect of ACh was partly inhibited by NG-monomethyl-l-argini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…This would explain why there are multiple receptor types present (an in-built redundancy of some receptors due to the importance of VIP-induced vasodilation). This is in agreement with previous studies which have shown endothelium-independent VIP-induced vasodilation of cerebral arteries (Duckles and Said, 1982;Lee et al, 1984;Gaw et al, 1991;Stojic et al, 2003). Additional evidence that VIP acts through each of these receptors in porcine basilar arteries is provided by the significant attenuation of VIPinduced vasodilation by VPAC 1 , VPAC 2 or NPR-C antagonists.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This would explain why there are multiple receptor types present (an in-built redundancy of some receptors due to the importance of VIP-induced vasodilation). This is in agreement with previous studies which have shown endothelium-independent VIP-induced vasodilation of cerebral arteries (Duckles and Said, 1982;Lee et al, 1984;Gaw et al, 1991;Stojic et al, 2003). Additional evidence that VIP acts through each of these receptors in porcine basilar arteries is provided by the significant attenuation of VIPinduced vasodilation by VPAC 1 , VPAC 2 or NPR-C antagonists.…”
Section: Discussionsupporting
confidence: 81%
“…Both VPAC 1 and VPAC 2 receptors have been shown to be expressed in equal amounts in human cerebral arteries regardless of endothelium; however, their location remains undetermined (Knutsson and Edvinsson, 2002). This finding concurs with previous experiments which have shown that VIP-induced vasodilation of cerebral arteries is independent of endothelium (Duckles and Said, 1982;Lee et al, 1984;Edvinsson and McCulloch, 1985;Nozaki et al, 1990;Gaw et al, 1991;Stojic et al, 2003). A third receptor has been identified to mediate VIP-induced relaxation of gastric smooth muscle: this is the natriuretic peptide clearance receptor (NPR-C) receptor (Akiho et al, 1995;Murthy et al, 2000).…”
Section: Introductionsupporting
confidence: 80%
“…The vasomotor function of parotid arteries from diabetic and control rabbits was examined in vitro by measurement of isometric tension, as described previously (17). In brief, parotid arteries were carefully removed and placed in oxygenated Krebs solution.…”
Section: Isometric Tension Recordingsmentioning
confidence: 99%
“…There are few studies reporting endothelium‐independent action of VIP in the different blood vessels, e.g. in human, bovine, rat and rabbit pulmonary artery, in porcine and canine coronary artery and rabbit facial artery (Beny et al., 1986; Greenberg et al., 1987; Nakashima et al., 1997; Stojic et al., 2003). On the contrary, in the rat and mouse aorta, rat mesenteric artery, porcine opthalmic artery endothelium‐dependent relaxation induced by VIP has been observed (Davies and Williams, 1983; Hattori et al., 1992; Bakken et al., 1995; Pomerleau et al., 1997).…”
Section: Discussionmentioning
confidence: 99%